Pharmacist-led academic detailing improves statin therapy prescribing for Malaysian patients with type 2 diabetes: Quasi-experimental design - Elnaem, Mohamed Hassan Abdelaziz; Nik Mohamed, Mohamad Haniki; Huri, Hasniza Zaman (Public Library of Science, 2019)
Objective Previous reports have highlighted the suboptimal utilization and prescription of statin ther- apy among patients with type 2 diabetes mellitus (T2DM) in the Malaysian clinical practice. This study aims to test the impact of a pharmacist-led academic detailing program on improving the overall statin therapy prescribing in Malaysian hospital and primary care settings. Methods As a quasi-experimental design with a control group and pre-tests., we examined 1,598 medical records of T2DM subjects in six healthcare facilities in the state of Pahang, Malaysia. In all study sites, there was a pre and post-intervention assessment of the percentage of appropriate statin therapy prescribing that complied with the clinical guidelines with no potential safety issues. The intervention was an academic detailing program offered to the health care providers in three study sites, while the other three sites served as the control group. A comparison of the overall percentage of appropriate statin therapy prescribing before and after the academic detailing was performed in all intervention and control sites. Results Overall, 797 medical records were examined in the pre-intervention phase, and 801 records were evaluated in the post-intervention phase. The academic detailing program was associated with a statistically significant difference in the proportion of appropriate statin therapy prescribing between the post-intervention phase compared to the pre-intervention phase (n = 246, 61.7% versus n = 188, 47.1%), p = 0.001. Whereas, the appropriate statin therapy prescribing in the control study sites experienced a modest change from 53.8% (214/398) to 56.7% (228/402), p = 0.220. The academic detailing showed significant increases in the proportions of appropriate statin therapy prescribing in both hospital and primary care settings. Conclusions The academic detailing program was found to be significantly associated with a positive impact on the overall statin therapy prescribing among patients with T2DM in Malaysian hospital and primary care settings.